Movoraunnahr Scholars of Islamic Law and Their Mature Works - Dr. Mohammad Sabuj; Dr. Abdumukhtor Rakhmanov (Researchparks Publishing, 2024)
A historical analysis of the origin of Islamic law in … It focuses on the great contributions made by the scholars of Central Asia who are often remained unacknowledged. This study shows how the scholars of this region have learnt and traelled to learn Islamic law and how their contribution originates and develops some of the key litereatueres of Islamic law.